Pelatihan Penggunaan Multimedia Cerdas dengan Artificial Intelligence (AI) pada Siswa SMKN 04 Oku - Sapitri, Hera; Subagia, Desky; Septian, M. Farras; Rezidan, M. Fadel; Sari, Enda Kartika (Indo-MathEdu Intellectuals Journal, 2026)
This community service activity aims to improve digital literacy, understanding of Artificial Intelligence (AI) concepts, and the skills of SMKN 04 OKU students in using smart multimedia creatively, productively, and responsibly. The activity was conducted in the form of training involving students in grades X and XI from several areas of expertise. The methods used included lectures to reinforce basic AI concepts, interactive discussions, demonstrations of the use of AI-based multimedia applications, and hands-on practice by participants. The activity was evaluated through pre-tests and post-tests to measure the increase in understanding, observations of student activity during the activity, and assessment of the multimedia results produced. The results showed an increase in students' understanding of basic AI concepts, their ability to use smart multimedia, and an increase in creativity in producing digital content that supports learning. In addition, students showed a more positive attitude towards the wise and ethical use of technology. Overall, this activity made a positive contribution to supporting the improvement of learning quality and the readiness of vocational school students in facing developments in digital technology.